Distal resection of sacrum for the rectal cancer recurrence - A. І. Sukhodolia; V. V. Kernychnyi; S. A. Sukhodolia; B. E. Li; І. І. Savchuk (Клінічна хірургія)
Distal resection of sacrum for the rectal cancer recurrence